Arquitetura deposicional e caracterização faciológica da FM. Guarda Velha no geossítio Toca das Carretas - Grupo Guaritas/Bacia do Camaquã - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The Guaritas Group represents an important sedimentary record of Cambrian age occurring in the central-south region of Rio Grande do Sul. Established at the top of the Camaqua Basin succession, the group is formed by fluvial, aeolian and alluvial deposits, in a rift type basin geological setting and subdivided in 5 main units represented by an extensive succession with more than 1.000 meters. At the Toca das Carretas, Caçapava do Sul/RS, the sedimentary rocks of the Guarda Velha Formation are exposed representing the basal unit, composed by sandstones and conglomerates from braided river systems with alluvial influence. Therefore, the present paper worked toward to the acknowledgement of the spatial relations amongst the sedimentary rocks outcrops in the area, recognizing the geometry and internal structures by using geological field methods such as geological mapping, detailed graphic logs, facies successions analysis, depositional architecture. Eventually, there was acquired around 100 m of sedimentary column corresponding three main sedimentary logs: TC-01 (A to E units), TC02 and TC-03. Eight distinct lithofacies were identified (Gm, Gcm, Gh, Gt, Sl, St, Sr and Fl) that forward to high energy braided fluvial systems characterized by bed load deposited by wide discharge oscillation, distinct flow regimes, sedimentary influx variation and accommodation space, caused under climatic and tectonic influence. The lithofacies are arranged in two facies associations: i) intermediary sheet flood and ii) proximal longitudinal bar channels. Those associations are related to the bedform formation and migration and longitudinal bar formation and are placed in a interval of longitudinal textural variation expressing coarse upwards tendency, suggesting episodes of high sedimentary influx as it reaches to the proximal region, influenced by the rework of alluvial sediments provenance. Paleocurrent data shows that the channel are oriented towards the basin trend NNE-SSW. The final product of this paper qualified the compilation of the data acquired to design a educational panel for tourist promotion unified to the geological information about the Toca das Carretas geosite.
Keywords: Formação Guarda Velha; Depósitos Fluviais; Arquitetura deposicional; Toca das Carretas; Guarda Velha Formation; Fluvial Deposits; Depositional Architecture; CNPQ::CIENCIAS EXATAS E DA TERRA